2019
DOI: 10.1186/s12877-019-1276-y
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in older patients: identifying the need for support by a community pharmacist

Abstract: Background The community pharmacist is a key player in medication reviews of older outpatients. However, it is not always clear which individuals require a medication review. The objective of the present study was to identify high-priority older patients for intervention by a community pharmacist. Methods As part of their final-year placement in a community pharmacy, pharmacy students conducted 10 interviews each with older adults (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
0
19
1
3
Order By: Relevance
“…Our comorbid patients were polymedicated at home: the number of home medications was 4.0 (1.0–7.3) and 6.0 (3.0–10.0) for COVID-19-positive and COVID-19-negative patients, respectively (p<0.0001), which is lower than that in the study by Beuscart et al 19 …”
Section: Discussioncontrasting
confidence: 70%
“…Our comorbid patients were polymedicated at home: the number of home medications was 4.0 (1.0–7.3) and 6.0 (3.0–10.0) for COVID-19-positive and COVID-19-negative patients, respectively (p<0.0001), which is lower than that in the study by Beuscart et al 19 …”
Section: Discussioncontrasting
confidence: 70%
“…The prevalence of polypharmacy is increasing, 4,6, mainly in patients above sixty-five years. [17][18][19][20][21] Multinational studies conducted showed that adults with advanced age are taking an average of 2-9 medications/day. 22 Aronson of the University of Oxford has reported that polypharmacy often advantageous and itself is not a noticeable problematic clinical issue.…”
Section: Polypharmacy and Quality Of Lifementioning
confidence: 99%
“…In Canada, the province of Ontario has over 170 pharmacists integrated into primary care team settings including Family Health Teams (FHTs, or interdisciplinary group practices) and Community Health Centres (CHCs) [ 22 ]. Within these teams, pharmacists engage in many direct patient care activities including medication management, identifying adverse medication usage, and patient education, notably through the delivery of medication reviews [ 23 , 24 ]. When working in a primary care team setting, pharmacists are typically paid a salary and as such are not remunerated on a fee-for-service basis for each medication review or other professional service activities [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacist-led medication reviews in primary care have been shown to improve management of chronic disease and help to avoid adverse effects that result from polypharmacy [ 3 ]. Medication reviews are also known to decrease the number of drug therapy problems and inappropriate medications by altering drug dosage, formulation and regimen [ 24 ].…”
Section: Introductionmentioning
confidence: 99%